2019
DOI: 10.1149/2.1011906jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Performance and Carbon Resistance Comparison between Tin, Copper and Silver-Doped Nickel/Yttria-Stabilized Zirconia Anodes SOFCs Operated with Biogas

Abstract: Traditional Ni/YSZ anode SOFCs were modified by Sn, Cu and Ag by an infiltration method to obtain Sn-Ni, Cu-Ni and Ag-Ni alloy anode catalysts on the anode. The obtained maximum power density of Ni/YSZ, Sn-doped Ni/YSZ, Cu-doped Ni/YSZ, and Ag-Ni/YSZ cells fuelled by simulated biogas (14 mL min −1 CH 4 , 7mL min −1 CO 2 and 7mL min −1 N 2 ) at 750°C were 0.101, 0.272, 0.085 and 0.102 W cm −2 respectively. Stability tests of SOFCs in biogas revealed that the stability of Sn-Ni/YSZ and Ag-Ni/YSZ cells in operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Hence, the long-term stability of the SOFCs under biogas fuel could be significantly improved by adding 1 wt% Sn to the Ni/YSZ anode. 122…”
Section: The Development Of Hydrocarbon-fueled Anodesmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the long-term stability of the SOFCs under biogas fuel could be significantly improved by adding 1 wt% Sn to the Ni/YSZ anode. 122…”
Section: The Development Of Hydrocarbon-fueled Anodesmentioning
confidence: 99%
“…133 Jiang et al also found that doping the Ni–YSZ anode with 1 wt% Ag reduced the MPD of the cell when operating under the condition of 50% CH 4 –25% CO 2 –25% N 2 , but the long-term stability could be greatly improved. 122 Wu et al further improved the relevant works about introducing Ag in the Ni–YSZ anode by the electroless plating method, instead of using the impregnation method. Also, it was found that the MPD of the SOFCs with the Ni–Ag–YSZ anode increased whether in H 2 , dry CH 4 or dry C 2 H 6 fuel.…”
Section: The Development Of Hydrocarbon-fueled Anodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tape casting is a wet forming method that involves the mixing of slurry and additives with some lamination and sintering steps. [193][194][195][196] The thickness of the layers can be controlled by using a doctor blade and adjusting slurry viscosity. The resultant layer varies between 10 and 1000 μm.…”
Section: Colloidal Deposition Techniquesmentioning
confidence: 99%
“…22,36 Several anode modification strategies have been tested with methane as representative of hydrocarbon fuel such as using Ni-free copper-ceria-based anodes, 5,15,[42][43][44] perovskites-based anodes, [45][46][47] substitution of the ceramic oxides, 48,49 and anode surface modification. 38,[50][51][52][53] In spite of the carbon affinity to Ni, Ni is still preferred due to its higher electrical conductivity, superior catalytic activity and compatibility with other SOFC layers. 22 As Ni/ScSZ cells have the similar properties to Ni/YSZ cells, whilst ScSZ has higher ionic conductivity, research work comparing these two anode materials has been widely reported, including the implementation of biogas as fuel.…”
Section: Introductionmentioning
confidence: 99%